PROPUESTA. A CULTURAL, YOUTH MAGAZINE (AND SOMETHING ELSE) IN ARGENTINA DICTATORSHIP - Luciani, Laura (Revista de Historia Social y de las Mentalidades, 2022)
This article analyzes the magazine Porpuesta, emerged in 1977 and with a circulation of twenty two issues, is considered a countercultural or youth publication, like others emerging in the argentina dictatorship (1976-1983). It focuses on his relationship with the Socialist Workers Party, to which it was linked since 1978, whit the aim of understanding this dynamic and restore it in the universo of militant political practices in repressive contexts. In this sense, a relational perspective is privileged that allow us to investigate the convergence of the objetives of those qho initially formed the magazine and the editorial projects of the party.
Keywords: Cultural Magazines; Youth; Argentine Dictatorship; Socialist Worker's Parties